Metachronous Malignant Fibrous HistiocytomaA Rare Case Report - Rawal, Gireesha (Iran J Pathol, 2018)
Malignant fibrous histiocytoma (MFH) is one of the most common types of soft tissue sarcomas in adults. Distant metastases are developed in 30–40% of patients with MFH, with the most common site being the lung. However, metachronous MFH has not been reported previously in literature. This report describes a case of a 30-year-old man, who had two metachronous thigh tumors, both of which were confirmed to be MFH on histopathology and immunohistochemistry evaluations. A contemporary multidisciplinary approach to therapy including surgery, radiation and chemotherapy was advocated. Two primary sites of MFH raised the possibility of a genetic abnormality that could predispose such a patient to develop multiple primary sites of the same tumor.